Pengaruh Inovasi Produk dan Kualitas Pelayanan terhadap Kepuasan Konsumen pada MD Café Nganjuk - Hidayatul Khoiriyah; Muhammad Alhada Fuadilah Habib (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
The increasingly tight competition between creative industries in the culinary sector requires creative industries to develop strategies to attract consumers so that consumer satisfaction arises, various product innovations are carried out and the quality of service is not yet fully felt by consumers. Therefore, this research raises the issue of product innovation and service quality on consumer satisfaction. The aim of this research is to (1) examine whether product innovation and service quality simultaneously have a positive and significant effect on satisfaction, (2) examine whether product innovation partially has a positive and significant effect on consumer satisfaction, (3) examine whether product innovation has a partial positive and significant effect on consumer satisfaction. partial positive and significant effect on consumer satisfaction. This research uses a quantitative approach with an associative type of research. The sampling technique used nonprobability sampling technique, precisely accidental sampling, with a sample size of 70 respondents. The types of data used are primary data and secondary data. Questionnaire data were analyzed using SPPS Version 25.0 by testing validity, reliability, multicollinearity, multiple linear regression, coefficient of determination, hypothesis testing (F test, T test), and classical assumption tests (normality, heteroscedasticity and autocorrelation tests). The results of this research show that, (1) Product innovation and service quality simultaneously influence consumer satisfaction, (2) Product innovation partially has a positive and significant influence on consumer satisfaction, (3) Product innovation partially has a positive and significant influence on consumer satisfaction.